Machining of titanium alloys and composites for aerospace applications - Zitoune, R.; Krishnaraj, V.; Davim, J. Paulo (Materials science forum, 2013)
A growing concern in the aerospace, automotive and biomedical industrial segments of the manufacturing industry is to build absolute reliability with maximum safety and predictability of the performance of all machined components. This requires development and deployment of predictive models for detailing the effects of varying machining parameters on fatigue life of machined components. The fatigue life is mainly affected by the residual stresses developed during the machining. Residual stresses are produced due to plastic deformation material while machining. The plastic deformation generates cracks and micro structural changes, as well as large micro hardness variations. Residual stresses have consequences on the mechanical behaviour, especially on the fatigue life of the workpieces. Residual stresses are also responsible for the machining distortion phenomenon of the machined parts which lead to difficulties during assembly. The literature detailing the effects of varying operating parameters on tool life when machining Titanium alloy is comprehensive, however, relatively little of this data refers to their effects on machined workpiece surface integrity particularly, residual stress generation and distortion created. Greater knowledge of the effects of operating parameters on surface integrity is critical to the acceptance of new environment, cutting path and cutting sequence strategies on machining of Ti6Al4V aerospace alloys to increase the functional requirements and fatigue life of the milled thin components. In this book four chapters have been included to address the above reported issues.